CD43Lo classical monocytes participate in the cellular immune response to isolated primary blast lung injury. Issue 3 (September 2016) - Barnett-Vanes, Ashton; Sharrock, Anna; Eftaxiopoulou, Theofano; Arora, Hari; Macdonald, Warren; Bull, Anthony M.J.; Rankin, Sara M.
Abstract : BACKGROUND: Understanding of the cellular immune response to primary blast lung injury (PBLI) is limited, with only the neutrophil response well documented. Moreover, its impact on the immune response in distal organs remains poorly understood. In this study, a rodent model of isolated primary blast injury was used to investigate the acute cellular immune response to isolated PBLI in the circulation and lung, including the monocyte response, and investigate distal subacute immune effects in the spleen and liver 6 hours after injury. METHODS: Rats were subjected to a shock wave (~135 kPa overpressure, 2 ms duration) inducing PBLI or sham procedure. Rat physiology was monitored, and at 1, 3, and 6 hours thereafter, blood, lung, and bronchoalveolar lavage fluid (BALF) were collected and analyzed by flow cytometry, enzyme-linked immunosorbent assay, and histologic examination. In addition, at 6 hours, spleen and liver were collected and analyzed by flow cytometry. RESULTS: Lung histology confirmed pulmonary barotrauma and inflammation. This was associated with rises in CXCL-1, interleukin 6 (IL-6), tumor necrosis factor α and albumin protein in the BALF. Significant acute increases in blood and lung neutrophils and CD43Lo/His48Hi (classical) monocytes/macrophages were detected. No significant changes were seen in blood or lung "nonclassical" monocyte and in natural killler, B, or T cells. In the BALF, significant increases were seen in neutrophils, CD43Lo monocyte-macrophages and monocyte chemoattractant protein-1. Significant increases in CD43Lo and Hi monocyte-macrophages were detected in the spleen at 6 hours. CONCLUSION: This study reveals a robust and selective response of CD43Lo/His48Hi (classical) monocytes, in addition to neutrophils, in blood and lung tissue following PBLI. An increase in monocyte-macrophages was also observed in the spleen at 6 hours. This profile of immune cells in the blood and BALF could present a new research tool for translational studies seeking to monitor, assess, or attenuate the immune response in blast-injured patients. Abstract : Supplemental digital content is available in the text.